2012
DOI: 10.5114/ninp.2012.31354
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the C677T variant of the methylenetetrahydrofolate reductase (MTHFR) gene in patients with migraine with or without aura – a preliminary report

Abstract: Frequency of the C677T variant in the MTHFR gene was similar in patients and controls. Significantly more frequent prevalence of PFO in migraine patients with aura (with homozygous recessive genotype of MTHFR probably suggests their common genetic basis. Hyperhomocysteinaemia was significantly more frequent in migraine patients with the C677T variant, which could be an additional risk factor of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
2
3
0
1
Order By: Relevance
“…8 Many attempts have been made to investigate concentrations of Hcy, as a well-known predictor for cardiovascular disorders, in patients suffering from migraine. 57 Our results seem to agree with a more recently published study in which it has been observed that women who suffer from migraine with T allele of MTHFR gene had significantly higher concentration of Hcy and lesser B12 (309.03 vs 314.36 pmol/L) and B9 levels in their serum samples in comparison with carriers of CC genotype. This hypothesis appeared to be substantiated by findings that found higher concentrations of Hcy in cerebrospinal fluid (CSF) of migraine suffers than controls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…8 Many attempts have been made to investigate concentrations of Hcy, as a well-known predictor for cardiovascular disorders, in patients suffering from migraine. 57 Our results seem to agree with a more recently published study in which it has been observed that women who suffer from migraine with T allele of MTHFR gene had significantly higher concentration of Hcy and lesser B12 (309.03 vs 314.36 pmol/L) and B9 levels in their serum samples in comparison with carriers of CC genotype. This hypothesis appeared to be substantiated by findings that found higher concentrations of Hcy in cerebrospinal fluid (CSF) of migraine suffers than controls.…”
Section: Discussionsupporting
confidence: 93%
“…56 A recent study by Szczygioł et al, who evaluated the frequency of C677T variant of MTHFR gene, and Hcy concentrations of 91 migraineurs, showed significantly higher proportion of hyperhomocysteinemia in patients with C677T variant than the others. 57 Our results seem to agree with a more recently published study in which it has been observed that women who suffer from migraine with T allele of MTHFR gene had significantly higher concentration of Hcy and lesser B12 (309.03 vs 314.36 pmol/L) and B9 levels in their serum samples in comparison with carriers of CC genotype. 58 However, due to the very low proportion of patients with aura in the current study we failed to explore vitamin B12 and MMA status in those with and without aura compared to controls.…”
Section: Discussionsupporting
confidence: 93%
“…Among the excluded studies, 1 study compared TTH patients with HC, 82 1 study compared a group of MA patients with a group of MO plus TTH patients (figures for MO alone were not provided), 83 1 study compared a migraine group (figures for MA and MO were not provided separately), with a HC group and group of TTH patients, but relevant figures were not provided for the HC group, 84 1 study provided relevant figures for PHD patients and patients with cerebral venous sinus thrombosis (figures for MA and MO were not provided separately), 85 4 studies did not provide homocysteine levels according to the subtype of migraine (figures were presented according to the presence or not of white matter lesions, 86,87 according to sex and anthropometric measurements, 88 according to genetic parameters 89 ), 5 studies were uncontrolled (either only patients with MA or only patients with MO were included, absence of a HC group), 90‐94 2 studies (evaluating the same group of patients) determined the presence of hyperhomocysteinemia in patients with MA and MO (comparative statistics and Hcy levels were not available), 95,96 1 study assessed the presence of hyperhomocysteinemia according to genetic parameters, 97 1 study did not present any relevant figures or statistical comparisons between MA and MO patients, 98 4 studies evaluated the presence of migraine according to not‐validated diagnostic criteria (according to self‐reported presence of migraine headache 99‐101 and severe headache 102 ), 2 studies were case series, 103,104 and 4 studies did not provide relevant information 105‐108 …”
Section: Resultsmentioning
confidence: 99%
“…Stwierdza siê tak¿e wystêpowanie wariantu C677T genu MTHFR (gen reduktazy metylotetrahydrofolianu), który jest kojarzony ze zwiêkszonym stê¿eniem we krwi homocysteiny, bêd¹cej potencjalnym czynnikiem ryzyka pojawienia siê migreny. Homozygoty wariantu C677T genu MTHFR wystêpo-wa³y natomiast czêoeciej u chorych na migrenê z aur¹ i dro¿nym otworem owalnym, bêd¹cym kolejnym przypuszczalnym czynnikiem przyczyniaj¹cym siê do rozwoju bólów migrenowych [24,25].…”
Section: A a B B S S T T R R A A C C T Tunclassified